2004
DOI: 10.1161/01.cir.0000142293.60725.18
|View full text |Cite|
|
Sign up to set email alerts
|

Electrocardiographic Features of Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy According to Disease Severity

Abstract: Background-The purpose of this study was to systematically study diagnostic and prognostic electrocardiographic (ECG) characteristics of arrhythmogenic right ventricle dysplasia/cardiomyopathy (ARVD/C). Methods and Results-The patient population included 50 patients with ARVD/C (27 males, 23 females; mean age 38Ϯ15 years). We also analyzed the ECG of 50 age-and gender-matched normal control subject and 28 consecutive patients who presented with right ventricular outflow tract (RVOT) tachycardia. Right bundle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 255 publications
(68 citation statements)
references
References 17 publications
(34 reference statements)
1
67
0
Order By: Relevance
“…In a pathological myocardial substrate, this can perpetuate the incidence of life-threatening arrhythmias. Other studies have suggested that up to 67% of individuals with ARVC present with palpitations, 32% present with syncope, 27% with atypical chest pain, 6% with right ventricular failure, and 6% may remain asymptomatic [22]. …”
Section: Diagnosis Of Arvcmentioning
confidence: 99%
See 4 more Smart Citations
“…In a pathological myocardial substrate, this can perpetuate the incidence of life-threatening arrhythmias. Other studies have suggested that up to 67% of individuals with ARVC present with palpitations, 32% present with syncope, 27% with atypical chest pain, 6% with right ventricular failure, and 6% may remain asymptomatic [22]. …”
Section: Diagnosis Of Arvcmentioning
confidence: 99%
“…The management of ARVC is focused on prevention of lethal events such as SCD [21,22]. High-risk groups with an increased risk of SCD should be identified.…”
Section: Management Of Arvcmentioning
confidence: 99%
See 3 more Smart Citations